2011
DOI: 10.1097/olq.0b013e3181ec51f1
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Testing for Syphilis in the United States: A Cost-Effectiveness Analysis of Two Screening Algorithms

Abstract: The Treponemal-First option costs slightly more and results in more unnecessary treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 23 publications
3
56
1
2
Order By: Relevance
“…Third, the results from this study do not address whether screening with a treponema-specific assay is clinically or economically advantageous compared to screening by RPR assay. Past reports have suggested advantages and limitations to both strategies (8,9), and further studies are needed. Interestingly, among the 303 serum samples tested in our study, 97 (32.0%) were positive by FTA assay versus 94 (31.0%) by the panel and only 66 (21.8%) by RPR assay.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the results from this study do not address whether screening with a treponema-specific assay is clinically or economically advantageous compared to screening by RPR assay. Past reports have suggested advantages and limitations to both strategies (8,9), and further studies are needed. Interestingly, among the 303 serum samples tested in our study, 97 (32.0%) were positive by FTA assay versus 94 (31.0%) by the panel and only 66 (21.8%) by RPR assay.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, initial setup costs as well as ongoing laboratory operational costs may be also be higher (49,50).…”
Section: Diagnostic Algorithmsmentioning
confidence: 99%
“…Owusu-Edusei conducted a cohort decision analysis to estimate the expected costs and effects of the traditional and reverse algorithms in a low-prevalence setting such as would be found in the United States (50). They demonstrated that, while the reverse algorithm resulted in the treatment of 99% of syphilis cases, it was more expensive overall because it resulted in a significantly higher number of follow-ups (three times as many) and overtreatment.…”
Section: Comparison Of the Three Algorithmsmentioning
confidence: 99%
“…With the increased availability of automated assays for treponemal antibodies, however, many laboratories have shifted to a "treponemal-first" algorithm for syphilis testing. The merits of the 2 approaches have been debated in the literature in terms of clinical utility and cost-effectiveness (1,2 ). The main difference between the 2 approaches is the identification of treponemal-positive, RPR-negative patients when a treponemal-first algorithm is used (3 ).…”
Section: To the Editormentioning
confidence: 99%